Implementing a Fitrah-Based Education Model in Islamic Religious Education in Elementary Schools - Noor Isna Alfaien; Maemunah Sa'diyah; Hasbi Indra; Budi Handrianto (ATTA`DIB, 2026)
Islamic Religious Education (PAI) lessons in schools play a strategic role in shaping students' faith, morals, and personalities. However, in practice, PAI learning is often cognitive, memorization-oriented, and pays little attention to differences in student potential and development. This study used a descriptive qualitative. Data were collected through interviews with PAI teachers, field observations, and photo documentation, then analyzed qualitatively to produce valid, practical, and contextual products. The results of this study indicate that the Fitrah-based education model aligns with the principles of the Qur'an and is able to increase the internalization of Islamic values ​​through learning oriented to faith, morals, and real-life experiences of students. During the learning design and implementation stages, PAI teachers created a learning syllabus. This syllabus was tailored to the needs of studentFikri Islamic Fitrah School. The planning was also adapted to the learning program, as Al-Fikri School uses a variety of activity methods. This diversity has supported the holistic development of students. It also helps balance students' intellectual, emotional, social, and personality development. Report-based evaluations can include reflective journals, portfolios, attitude observations, and project assessments. Students have benefited from the fitrah learning model. Of the 32 students, 29, or 90.63%, stated that it significantly helped them understand Islamic teachings more deeply. Furthermore, 93.75% of students reported an increase in spiritual and moral awareness. Thus, the fitrah learning model can be considered highly effective.